A Study on the Textbook Composition and Teacher Perception on 'The Function Represented by a Parameter' - Seong Hyun Yang (Korea Society of Educational Studies in Mathematics, 2022)
Clarity and consistency of terms are more important in mathematics than in any other discipline. Mathematics terminology can be an essential clue to understanding a mathematical concept. Moreover, it can evoke images related to the concept both during the learning process and after learning. However, the evoked image may fail to match the original mathematical concept accurately if a student has a misconception about a specific mathematical term. This paper specified the ambiguity and inconsistency of the expression "the function represented by a parameter" used in textbooks. Further, it investigated the teachers' perceptions caused by the phrase. Teacher responses in a survey showed that teachers perceived the words in various ways, and some teachers demonstrated mathematical misconceptions. Additionally, the teachers recognized the need to revise the phrase, "the function represented by a parameter." Our study implicates that unclear and inconsistent uses of mathematical terms in textbooks and teacher's guide books might contribute to teacher misunderstandings, which can directly or indirectly affect students.